Spiritual inspiration of Character Cossacks (based on the novel "Roaring Ukraine" by P. Panch) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
In the article we research outstanding features in kosaks' characters in the nov-el of P. Panch "Homonila Ukraina". We pay attention to those features which allowed kosaks to influence noticeably their environment and enemies, be invincible in battles. It is shown that all outstanding kosaks' way of thinking, acting and living is directed to gain the best good for Ukraine and Ukrainians.
Keywords: characters; kosaks